Cultural memories: the geographical point of view - Meusburger, Peter; Wunder, Edgar (Knowledge and space, 2011)
Focusing on the role of spatiality and places, this volume explores cultural memories -- social constructions of the past which allow human beings to orient themselves in time and space. Theoretical considerations are presented, as well as three case studies that illustrate the concepts discussed.